Perancangan Digital Handbook sebagai Media Informasi untuk Meningkatkan Akses Audiens APIKES Iris - Annisa Soleha Z; Willy Bachtiar (Journal of Creative Student Research, 2026)
This research discusses the design of the APIKES Iris handbook digital information media which is behind the problem of information access, where the available website is still desktop oriented and the existing social media has not been utilized as an optimal information media. The method used is qualitative with data collection through observation, trial, in-depth interview, and documentation. The data obtained is then analyzed using data reduction techniques by filtering, grouping, and focusing relevant information. This research aims to transform complex information through content curation techniques into more concise, structured, and practical information. The media design process is carried out using the theory and approach of User Centered Design (UCD) to ensure that the media developed is in accordance with the needs of users and organizational goals. Research results show that handbook digital information media is able to collect information that was previously scattered centrally into one media that has been integrated and responsive for both mobile and computer users. In addition, the implementation of UCD proves that the approach can not only be applied in application development, but also in the design of digital information media. This research also shows that the aspect of media design and proper information preparation is able to produce a more functional information media.